PENGARUH STRUKTUR BAHASA ARAB TERHADAP BAHASA INDONESIA DALAM TERJEMAHAN AL-QURʼAN - Yayan Nurbayan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
The process of translation in fact gave birth to a sociolinguistic phenomenon like bilingualism when the structure of a language that translated influence on the translation. This paper examines the translation of the Koran, which follows the pattern of the structure of the Arabic language in terms of word order (sequence pattern) element of Arabic and Indonesian. Based on the analysis of the function, the result of translation is not necessarily a literal translation has the same syntactic pattern with the source text. Indonesian function often different in sentence patterns with sentence patterns of Arabic, although it is the literal translation of the Arabic sentence. It happened because of the workings of the Arabic grammarians differ from Indonesian linguist in analyzing its function. DOI: 10.15408/a.v1i1.1128